Proactive Digital Transformation Imperative (PDTI): The Role of Capabilities Strategic Digital Business in MSMEs - Daryono Daryono; Setyawati Gunawan Ratna; Setyorini Gunawan Diah (E3S Web of Conferences)
This research examines the relationships between organizational capabilities, digital business strategy, Proactive Digital Transformation Imperative, and organizational performance in Indonesian MSMEs. It aims to provide insights into how these factors interact to drive performance outcomes in the context of digital transformation, aligned with the Sustainable Development Goals (SDGs). Design/methodology: Based on this analysis, a theoretical framework was developed and empirically tested using survey data from Indonesian MSMEs. Findings: The results indicate that organizational capabilities have a significant positive impact on both digital business strategy and Proactive Digital Transformation Imperative. Furthermore, digital business strategy and Proactive Digital Transformation Imperative both positively influence organizational performance. The findings suggest that solid organizational capabilities can enhance digital transformation efforts and strategic outcomes. Practical implications: The findings highlight the importance of developing robust organizational capabilities to support effective digital business strategies and transformation initiatives. Managers should focus on building digital competencies and flexible organizational structures to drive performance improvements. Originality/value: This research contributes to the literature by integrating organizational capabilities, digital business strategy, and Proactive Digital Transformation Imperative into a comprehensive model explaining organizational performance.